An Overview of Recent Advances on Pathophysiology, Diagnosis and Treatment of Trigeminal Neuralgia - Montano, Nicola; Rapisarda, Alessandro (New Horizons in Medicine and Medical Research Vol. 2, 2022)
Trigeminal Neuralgia (TN) is the most frequent neuropathic facial pain with important consequences on quality of life of the affected patients. Neurovascular conflict (NVC) has been recognized as the cause of the classical form, but TN can be secondary to other diseases. In the idiopathic form of TN no NVC and other causes can be identified. However the exact cascade of events and pathways that lead to TN are not completely understood, even if recent studies suggests that an inflammatory environment may play role. The introduction of new magnetic resonance imaging (MRI) techniques, such as voxel-based morphometry, diffusion tensor imaging and three-dimensional time-of-flight magnetic resonance angiography has provided new insight about the TN pathogenesis. Moreover, the combination of these advanced MRI sequences with volume-rendering softwares and neuronavigation techniques showed a significant impact on the surgical outcome of patients submitted to microvascular decompression. In fact, TN management is pharmacological from the beginning, nevertheless TN can progressively become unresponsive to drugs necessitating multimodal treatment. Despite numerous available approaches, the results are not completely satisfying and the need for more effective drugs led to the development of new molecules and pharmacological protocols. Moreover, some patients may become drug resistant needing a surgical procedure or radiation treatment. Nonetheless, pain recurrence after one or more surgical operations is also frequently seen and other rescue treatments, such as neuromodulation, may be required to handle the symptoms. These facts reflect the lack of a precise understanding of the TN pathogenesis. The aim of this work was to review the recent literature about the pathogenesis, diagnosis, medical and surgical treatments and discuss the significant advances in all these fields.